Sebuah Pemikiran Teori Hukum Murni Hans Kelsen - N, Yunda Rahayu; Rizqia Aufa H; Rohima, Syifa (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
The law as a fundamental element in societal life functions as a rule that regulates interactions between individuals and institutions. Hans Kelsen's Pure Theory of Law is one of the most significant contributions to the development of legal theory by Austrian legal scholars. This theory emphasizes the separation between law and morality, as well as the influence of politics or ideology on legal analysis. This article discusses the background of Kelsen's thought, the development of his theory, and its relevance in the context of modern law. This research uses a normative legal research method and is conducted using a study of literature that involves various references to journals, books, and recent articles. Kelsen's Pure Theory of Law has several key elements that are characteristic of it and distinguish it from other legal theories. This theory helps to create a scientific and objective approach to understanding the law, as well as providing a foundation for the application of law that is consistent and just. However, this theory also faces criticism from various groups, especially because it is considered too formalistic and neglects values of justice.